Technical innovations and their representations in post-modern arts (Op art as a model) (Al-Academy, 2024)
Technical innovations as distinct activities appear and affect within a social structure, adding pressure burdens that constantly dictate a change in human forms and relationships and help the emergence of new and unexpected situations that are reflected in the aesthetic data and technical experience of these societies. All aspects of science, including human approaches, are affected by technological development. This prompted the artist to search for what art is and its new patterns, which depend on the link between the elements of space, light and movement in order to create the new kinetic beauty that evokes sensations at the same time. The current research consists of four chapters. The first chapter of the research included a definition of the research problem, which was determined by answering the following question (How did the technical innovations contribute to crystallizing new methods in postmodern arts (Op art) as a model?) And the importance of the research. As for the aim of the research, it was determined by revealing (the representations of technical innovations in postmodern arts (Op art as a model) and defining the terms. As for the second chapter, it included three topics such as the first technical innovations, and the second topic features of postmodern arts, while the third topic dealt with Representations of technical innovations in visual art, while the third chapter contains research methodology, procedures, and society, and the selection and analysis of the sample, which are (5) artworks. The fourth chapter contains the results of the research, the most important of which are: technical innovations contributed to the development of postmodern arts in general and Op art in particular , Fit the opportunity for the artist to control the formations of the artwork, as I worked geometric shapes, lines and black colors, white and blue to add simulated element formulations works of art through the ideas and visions of art associated with the spirit of modern times, and then the conclusions and recommendations of the proposals